Sociocultural determiners of scientific activity transformation; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Rubanov V. G. Vitaliy Georgievich; Rubanova E. V. Elena Vitalievna; Zeremskaya Yu. A. Yuliya Aleksandrovna; Cheng Xinhan; Shcherbinin A. Aleksey (2016, 2016)
Title screen